Inter-hemispheric frontal alpha synchronization of event-related potentials reflects memory-induced mental fatigue. (13th July 2017) - Liu, Xinyang; Liu, Juntao; Duan, Feng; Liu, Rui; Gai, Shuping; Xu, Shengwei; Sun, Jianhui; Cai, Xinxia
Highlights: We assessed bilateral ERP alpha synchronization changes in memory-induced fatigue. Frontal ERP alpha coherences were higher than other brain regions in memorization. Frontal ERP alpha coherences decreased from the non-fatigued to fatigued state. Bilateral frontal ERP alpha coherence can be used to assess memory-induced fatigue. Abstract: Mental fatigue is often associated with continuous brain activities in our daily life. It can diminish efficiency and increase errors. However, the related physiological features are still not clear and under exploration. The present study investigated changes of inter-hemispheric synchronization in event-related potentials (ERPs) due to mental fatigue during sustained memory processing. Twenty-six participants performed a continuous two-back memory task for around 2.5 h. Prefrontal and frontal synchronies in the alpha frequency band (8–13 Hz) were analyzed because of their close relationships with memory functions. Coherence was used to examine bilateral synchronization changes of ERP power and phase. We compared ERP coherences in both non-fatigued and fatigued states. We also observed the variation of ERP coherences during the continuous task. High overlaps of inter-hemispheric ERP waveforms were observed at prefrontal and frontal cortex in both non-fatigued and fatigued conditions. During the whole experimental procedure, ERP alpha coherences at frontal regions (FP1-FP2 and F3-F4) were significantly higher than at central (C3-C4), parietal (P3-P4) and occipital (O1-O2) regions. Alpha synchronization in anterior electrode pairs showed significant declines with increasing mental fatigue during the memory task. Our findings about changes in frontal ERP alpha synchronization might be used as biomarkers to assess mental fatigue induced by prolonged memory demands.